2016
DOI: 10.15713/ins.jmrps.73
|View full text |Cite
|
Sign up to set email alerts
|

A population-based retrospective study of zygomatic air cell defect in Bengaluru

Abstract: Aim:The aim of the study is to determine the occurrence, radiographic appearance, disparities, features and establishing predominant site, and form of zygomatic air cell defect (ZACD) among the population in Bengaluru. Materials and Methods:The orthopantomographs of 600 dental hospital outpatients were examined to estimate the occurrence and characteristic features of the ZACD. Results: ZACD was evaluated to be present in 16 patients with male predominance. Unilateral (69%) and unilocular appearances (56%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Another study conducted by Orhan et al reported the same prevalence for both forms [ 17 ]. The same variation was also detected, where some studies detected a high prevalence of unilateral [ 21 , 36 ]. In contrast, another study by Serindere and Belgin reported a higher occurrence of bilateral [ 37 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Another study conducted by Orhan et al reported the same prevalence for both forms [ 17 ]. The same variation was also detected, where some studies detected a high prevalence of unilateral [ 21 , 36 ]. In contrast, another study by Serindere and Belgin reported a higher occurrence of bilateral [ 37 ].…”
Section: Discussionsupporting
confidence: 59%
“…Regarding the lesion type and side, this study reported a high prevalence of bilateral (53.4%) and unilocular (47.6%) lesions. A high variation was noted among studies in relation to the lesion type, where one study reported the unilocular as a dominant form [ 21 , 35 , 36 ]. In contrast, others reported the multilocular as a dominant form [ 22 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,8,12 PAT can be observed in orthopantomography, which was considered the initial method for examining AT due to its low cost and low radiation dose compared with tomographic imaging. 1,2,4,11,[13][14][15][16][17][18][19][20][21][22][23][24] However, the latter is not likely to overlap with anatomical structures as in conventional imaging, and they exceed the diagnostic accuracy in the evaluation of air spaces in the temporal bone. 3,6,5,10,25,26 The roof of the temporal mandibular fossa (MF) is a thin sheet of bone separating the temporomandibular joint (TMJ) from the middle cranial fossa, with thickness ranging from 0.2 to 4.0 mm.…”
Section: Introductionmentioning
confidence: 99%